Primary Radical Surgery in Elderly Patients With Epithelial Ovarian Cancer: Analysis of Surgical Outcome and Long-Term Survival. Issue 1 (1st January 2010) - Fotopoulou, Christina; Savvatis, Konstantinos; Steinhagen-Thiessen, Elisabeth; Bahra, Marcus; Lichtenegger, Werner; Sehouli, Jalid
Abstract : Objective: Geriatric population life expectancy is increasing and so is the incidence of epithelial ovarian cancer (EOC) in elderly women. The aim of our study was to determine the impact of radical cytoreductive surgery, the cornerstone of clinical management in primary EOC, in this population with special regard to the associated morbidity. Methods: Through a pooled data analysis, cancer-related patient characteristics, intraoperative tumor pattern, and surgical and clinical outcomes were evaluated according to a validated documentation data collection tool. Kaplan-Meier curves were calculated for overall survival (OS). The Cox regression analysis was performed to identify independent predictors of mortality. Results: One hundred one EOC patients older than 69 years (mean [SD] age, 75.54 [4.49] years) were evaluated. The mean (SD) follow-up period was 22.63 (22.92) months. Advanced International Federation of Gynecology and Obstetrics stage III (60.4%) was the most common tumor stage. A complete tumor resection was achieved in 45 patients (44.6%) with an associated complication rate of 40.6%. The postoperative mortality was 6%. The mean OS was 47.29 months (95% confidence interval, 36.24-58.34). The multivariate analysis identified age older than 75 years, incomplete tumor resection, and absence of adjuvant chemotherapy to negatively affect OS. Conclusions: Radical surgery for primary EOC obtaining complete tumor resection is associated with a significantly prolonged OS in elderly patients (≥70 years). The increased postoperative morbidity must be considered, underlining the high requirement for special interdisciplinary postoperative management in this special collective.